Forward Guidance Contracts - Hans Gersbach; Volker Hahn; Yulin Liu (Center for Economic Studies and ifo Institute (CESifo), 2015)
We examine “Forward Guidance Contracts”, which make central bankers' utility contingent on the precision of interest-rate forecasts for some time. Such Forward Guidance Contracts are a exible commitment device and can improve economic performance when the economy is stuck in a liquidity trap. Utilizing the New Keynesian Framework, we establish the properties of simple renewable Forward Guidance Contracts and characterize the contracts that the government wants to offer repeatedly. These contracts create favorable tradeoffs between the efficacy of forward guidance at the zero bound and the reduced exibility in reacting to future events, when the zero bound on nominal interest rates constrains the central banks' choice. We discuss how Forward Guidance Contracts can be used when there is uncertainty about natural real interest-rate shocks, a situation which typically calls for moderate incentive intensity. Finally we explore alternative contractual environments.
Keywords: E31; E49; E52; E58; 330; forward guidance; zero lower bound; central banks; incentive contracts; transparency